(untitled) (Bulletin of criminological association of Ukraine, 2023)
Attention is focused on the fact that the key types of crimes currently investigated by the FBI are: crimes related to violations of federal laws. This includes such crimes as: bank robbery, extortion, and human trafficking; organized crime. At the same time, FBI investigations can go beyond the borders of a particular state; crimes committed by public officials, in particular: bribery, embezzlement, fraud, abuse of power, etc.; crimes related to the violation of human civil rights, in particular, the FBI investigates crimes that were committed on the basis of racial, religious hatred, etc.; crimes committed through the use of information technology, such as hacking, identity theft, and other forms of online fraud; crimes against National Security, in particular: espionage, terrorism and international organized crime. It also investigates violations of import and export control laws, as well as the international arms trade. The following positive aspects of the experience of the US Federal Bureau of Investigation, which can be used to improve the work of the State Bureau of Investigation of Ukraine (SBI), are highlighted, including the following: 1) high level of professionalism of FBI agents. In particular, the Bureau can improve its work by recruiting professionals from other fields, while ensuring constant and systematic training and support of existing employees; 2) in the process of its activity, the FBI is actually not limited in resources (financial, material, technical, etc.), which gives them the opportunity not only to quickly investigate any crimes, but also to effectively prevent their commission; 3) The FBI actively cooperates with other law enforcement agencies around the world. The Bureau constantly develops international partnerships and exchanges experience for more effective counteraction to transnational crime; 4) The Bureau uses advanced technologies in its operations, including data analytics, cyber security and other tools. The FBI can invest in the development of modern technologies to improve the quality of its investigations and optimize work processes; 5) despite the high level of autonomy and independence, the FBI maintains a high standard of openness and transparency in its work, which contributes to maintaining public trust.